MYSTERIOUS WAYS OF KYIV SURGERY (PART 1). UNIVERSITY HOSPITAL - Dubenko, Dmytro (The Ukrainian Scientific Medical Youth Journal, 2020)
The article highlights the historical aspects of the development and formation of surgery in Kyiv in the 19th and 20th centuries. Based on archival documents, the chronology of the creation of St. Volodymyr Kyiv University faculty surgical hospital is shown. Some facts of the hospital's existing during the Russian Empire, the revolutionary events of 1917-1921, Soviet period and the Nazi occupation of Kyiv in 1941-1943 are described. The research presents biographical facts about the chiefs and employees of the faculty surgical hospital: Yevgen Chernyakhivsky, Yuriy Voronyi, Vira Gedroyts, Mykola Volkovych, Olexiy Lazurenko.